نزع السلاح دليل أساسي - United Nations Office for Disarmament Affairs (United Nations, 2018)
Conceived as a comprehensive introduction to a field central to the work of the United Nations, Disarmament: A Basic Guide aims to provide a useful overview of the nuanced challenges of building a more peaceful world in the twenty-first century. It was written with the general reader in mind and it strives to be accessible without downplaying the complexity of the issues it explores. This fourth edition includes updated figures, tables and treaty statuses; new analysis of the key developments since 2012; discussion of two recently agreed legal instruments, the Arms Trade Treaty and the Treaty on the Prohibition of Nuclear Weapons; and a new chapter on emerging threats from cyber weaponry, unmanned combat aerial vehicles and lethal autonomous weapons systems.